القصدية في كتب النحو القرآني كتابي (الجواري والأنصاري أنموذجا) - الكوام, ندى سامي ناصر; الظالمي, سيماء فاضل (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
Since the inception of Arabic grammar, grammarians have been keen to establish a grammatical rule for every phrase or sentence, relying on Arabic intuition. If they found a phrase that did not fit the rules, they had established based on the prevailing Arabic language, they interpreted it based on estimation and interpretation. This is from the perspective of colloquial Arabic speech. However, from the perspective of the holiest book (the Holy Quran), they used the same methods of estimation and interpretation. For example, when there was no predicate for the subject, they interpreted this based on estimation. The Holy Quran is the word of God, and every word has an intention. When a predicate is not mentioned in a Quranic verse, the omission must be intentional, because the intention conveyed by the phrase differs from the intention in the case of mention. There is no doubt that this is due to a profound and deliberate divine wisdom. In this research, we attempted to deduce the intention behind Quranic grammar through a simple induction of the books "The Theory of Quranic Grammar by Ahmad Makki Al-Ansari" and "The Grammar of the Quran by Al-Jawari," and to explore the views of commentators and grammarians on this matter. The research is divided into three parts: the first is theoretical, in which I present the nature of intention and its types. The second is practical, including applied models from Al-Ansari's book Theory of Quranic Grammar. The third includes applied models from Al-Jawari's book Grammar of the Quran.